Návrh IS pro podporu firemních procesů - Hrušecký, Jozef (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Ciežom bakalárskej práce "Návrh IS pro podporu firemních procesú" je posúdenie súčasného IS firmy a návrh možných zmien spojených s ich ekonomickým zhodnotením.

The goal of Bachelor's thesis "Proposal of IS for support firm processes" is an analysis of current IS of the company and proposal of possible changes unified with economical appreciation.
Proposal of IS for support firm processes
Keywords: Informačný systém SWOT analýza Porterova analýza piatich konkurenčných síl; Information system SWOT analysis Porter’s five forces analysis